A micromechanics-based non-local damage to crack transition framework for porous elastoplastic solids. (April 2020) - Leclerc, Julien; Nguyen, Van-Dung; Pardoen, Thomas; Noels, Ludovic
Abstract: The failure process of ductile porous materials is simulated by representing the damage nucleation, growth and coalescence stages up to crack initiation and propagation using a physically-based constitutive model. In particular, a non-local damage to crack transition framework is developed to predict the fracture under various loading conditions while minimising case-dependent calibration process. The formulation is based on a discontinuous Galerkin method, making it computationally efficient and scalable. The initial stable damage process is simulated using an implicit non-local Gurson-Tvergaard-Needleman (GTN) model ensuring solution uniqueness beyond the onset of softening. Once the coalescence criterion is satisfied, which can physically arise before or during the softening stage, a cohesive band is introduced. Within the cohesive band, a void coalescence-based governing law is solved, accounting for the stress triaxiality state and material history, in order to capture the near crack tip failure process in a micromechanically sound way. Two coalescence models are then successively considered and compared. First, with a view to model verification towards literature results, a numerical coalescence model detects crack initiation at loss of ellipticity of a local model, and the crack opening is governed by ad-hoc parameters of the GTN model. Alternatively, the Thomason criterion is used to detect crack nucleation during the softening stage while the Thomason coalescence model governs the crack opening process. This latter model is able to reproduce slant and cup-cone failure modes in plane-strain and axisymmetric specimens, respectively. Highlights: A damage to crack transition framework is developed for ductile failure. A non-local porous plastic model combines the Gurson and Thomason models. A cohesive band model captures triaxiality effects during crack propa-gation. Slant fracture is captured for plane strain specimen in agreement with experiments. Cup-cone fracture is predicted for round bars in agreement with exper-iments.